UTILIZATION OF LEMONGRASS EXTRACT (CYMBOPOGON CITRATUS) AGAINST THE ANTIOXIDANT CONTENT AND SENSORY PROPERTIES OF DARK CHOCOLATE PRODUCTS - Pratiwy, Amelya Eka; Kusumaningrum, Intan; Aminullah, Aminullah (Universitas Djuanda, 2019)
The use of lemongrass extract on dark chocolate products is a diversification of processed chocolate products to increase the antioxidant content and sensory pofile. This research aims to study the effect of comparison chocolate and spice extracts, interaction chocolate and spice extracts comparison of lemongrass to antioxidant compounds and organoleptic characteristics, and to know the chemical properties of selected products. This study consisted of two phases: the first stage is to prepare lemongrass extract with the steam distillation method, the second stage is to make products that include chocolate melting, mixing and molding, then antioxidant tests and organoleptic to determine the selected products with quality sensory tasts and hedonic tests/preferences, chocolate product selected test chemical (moisture, ash, fat, protein, carbohydrate, and calories). The results of the study by testing the antioxidant different uses of chocolate on antioxidant components showed couverture chocolate types have a higher %inhibition compared to the chocolate kind of compound, the higher the addition of lemongrass extract, the higher antioxidant activity, in the organoleptic tests showed significantly different the parameters of aroma, taste and after taste, but not significantly different from the parameters of melt, interactions between different types of chocolate use, as well as the ratio of chocolate and lemongrass extract significantly influence antioxidant activity, but do not significantly affect organoleptic test results, couverture chocolate products with the addition of 0.3% spice extract are declared as selected products with antioxidant activity of 83.594%, 1.41% moisture, 1.04% ash, 20.96% fat, 3.40% protein content, 73.19% carbohydrates and total calories 495 kcal/100 grams.